2008
DOI: 10.1002/polb.21581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, crystallization kinetics, and melting behavior of poly(ethylene succinate) copolyester containing 10 mol % butylene succinate

Abstract: Copolyester was synthesized and characterized as having 89.9 mol % ethylene succinate units and 10.1 mol % butylene succinate units in a random sequence, as revealed by NMR. Isothermal crystallization kinetics was studied in the temperature range (T c ) from 30 to 73 C using differential scanning calorimetry (DSC). The melting behavior after isothermal crystallization was investigated using DSC by varying the T c , the heating rate and the crystallization time. DSC curves showed triple melting peaks. The melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…In the 13 C‐NMR spectrum of PEBSA 50/50, the carbonyl carbons were split into four peaks, which areas were utilized for the determination of the triads possibility, composition and the ester sequence distribution in this copolyester. Based on the analysis of carbonyl carbons, PEBSA 90/10 copolyester was characterized as having 89.9 mol % ethylene succinate (ES) units and 10.1 mol % BS units in a random sequence 34. Only enlarged 13 C‐NMR spectrum of the carbonyl carbons of PEBSA 90/10 copolymer is replotted in Figure 1 for the comparison with PES/PBS 90/10 blend.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 13 C‐NMR spectrum of PEBSA 50/50, the carbonyl carbons were split into four peaks, which areas were utilized for the determination of the triads possibility, composition and the ester sequence distribution in this copolyester. Based on the analysis of carbonyl carbons, PEBSA 90/10 copolyester was characterized as having 89.9 mol % ethylene succinate (ES) units and 10.1 mol % BS units in a random sequence 34. Only enlarged 13 C‐NMR spectrum of the carbonyl carbons of PEBSA 90/10 copolymer is replotted in Figure 1 for the comparison with PES/PBS 90/10 blend.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies of isothermal crystallization kinetics of PEBSA copolymers were reported in our most recent works 34, 35. For brevity, only the kinetic analysis of PES/PBS 90/10 blend is presented here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two or three decades, there has been considerable interest in the development of biodegradable and biocompatible polymers. Among the synthetic biodegradable polymers, aliphatic polyesters, poly(butylene succinate) (PBS),1 polylactide (PLA),2 and Poly(amino acid)3, 4 have been thoroughly investigated and use in the field of pharmaceutical, agricultural, and biomedical materials 5–7…”
Section: Introductionmentioning
confidence: 99%
“…Combining self‐nucleation and nonisothermal temperature programs facilitates the expansion of the temperature range where growth rate data are measurable. Using this approach, Lu et al recently estimated the G values of PETSA 80/2012 and PEBSA 90/1018 between the melting ( T m ) and the glass transition ( T g ) temperatures, where PEBSA is a copolymer of ethylene succinate and butylene succinate. Those continuous growth rates fitted well with the data points measured in the isothermal experiments.…”
Section: Introductionmentioning
confidence: 99%